2017
DOI: 10.4168/aair.2017.9.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Related Outcomes in Patients Initiating Extrafine Ciclesonide or Fine-Particle Inhaled Corticosteroids

Abstract: PurposeExtrafine-particle inhaled corticosteroids (ICS) have greater small airway deposition than standard fine-particle ICS. We sought to compare asthma-related outcomes after patients initiated extrafine-particle ciclesonide or fine-particle ICS (fluticasone propionate or non-extrafine beclomethasone).MethodsThis historical, matched cohort study included patients aged 12-60 years prescribed their first ICS as ciclesonide or fine-particle ICS. The 2 cohorts were matched 1:1 for key demographic and clinical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…We compared extrafine-particle inhaled corticosteroid (ICS) to larger fine-particle ICS – a comparison that has been investigated previously 14. We found that extrafine-particle ICS was associated with similar or better asthma-related outcomes than a larger fine-particle ICS at significantly lower prescribed doses 15. In this study, we aim to compare the performance of exact matching with that of PSM by applying these methods in this historical cohort study, including both balance diagnostics and the impact on the primary endpoint of the original study.…”
Section: Introductionmentioning
confidence: 99%
“…We compared extrafine-particle inhaled corticosteroid (ICS) to larger fine-particle ICS – a comparison that has been investigated previously 14. We found that extrafine-particle ICS was associated with similar or better asthma-related outcomes than a larger fine-particle ICS at significantly lower prescribed doses 15. In this study, we aim to compare the performance of exact matching with that of PSM by applying these methods in this historical cohort study, including both balance diagnostics and the impact on the primary endpoint of the original study.…”
Section: Introductionmentioning
confidence: 99%
“…Результаты аналогичного анализа с выделением в отдельную группу больных, получавших циклесонид, были опубликованы в 2017 г. [41]. В каждой из групп (по 1244 пациента) основные демографические и клинические показатели были сопоставимы, но в группе получавших циклесонид число связанных с БА госпитализаций превышало этот показатель в группе сравнения.…”
Section: влияние циклесонида на мдп у больных баunclassified
“…В каждой из групп (по 1244 пациента) основные демографические и клинические показатели были сопоставимы, но в группе получавших циклесонид число связанных с БА госпитализаций превышало этот показатель в группе сравнения. Анализ результатов терапии в течение 1 года показал, что при назначении циклесонида (средняя доза -160 мкг ГКС в пересчете на флутиказон) количество обострений было существенно ниже, пациенты имели значительно большие шансы достичь и поддерживать контроль заболевания, реже требовалось увеличение суточной дозы ИГКС, при средней суточной дозе циклесонида в пересчете на флутиказон на 1/3 ниже, чем в группе сравнения [41].…”
Section: влияние циклесонида на мдп у больных баunclassified
“…To this end, we aimed to evaluate the clinical utility of several asthma database outcomes used in our previous studies. 16 18 In particular, we investigated the following: 1) how useful these database outcomes were for providing insights into asthma control, compared to information gained from patient-reported questionnaires; 2) how well the database outcomes performed in assessing response to effective treatment; and 3) how well the database outcomes predicted future asthma exacerbations. To do this, we used database electronic medical records (EMRs) and linked questionnaire data from a large population of patients with asthma managed in routine primary care in the UK.…”
Section: Introductionmentioning
confidence: 99%